Characteristics of Post-Neurosurgical Nosocomial Bacterial Meningitis in Adults: a retrospective Cross-Sectional Study - Irfanullah Shah, Muhammad Aslam Shaikh, Khalid Mehmood (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To analyze the characteristics of Post-neurosurgical nosocomial bacterial meningitis in adults Study design: A retrospective cross-sectional study Place and duration: Riyadh Care Hospital/ National Care Hospital, from July 2005 to June 2010 then 2013 to 2018. Methodology: Over ten years, sixty-two patients above the age of 16 years who suffered from Post-neurosurgical nosocomial bacterial meningitis were evaluated by collecting clinical data. The cases were divided into two categories, the first one from July 2007 to June 2012 and second one from August 2013 to July 2018. Results: Among the 62 patients, there were 43 males and 19 females with post-neurosurgical nosocomial bacterial meningitis. It was recorded in the first group that the percentage of post-neurosurgical nosocomial meningitis in all culture-proven adult bacterial meningitis was 12 percent and for the second group it was seen to be 27 percent. The most constant clinical characteristics were fever and gradual consciousness disruption, which may be related to various postoperative neurosurgery issues. The most prevalent pathogens were recorded to be pseudomonas aeruginosa, staphylococcus aureus, coagulase-negative staphylococcus, Acinetobacter baumannii, and lastly, Escherichia coli. During the second era, there was a rise in polymicrobial illnesses and multi antibiotic resistance. Mortality was 22% in the first group of the study and 36% in the second group of the study. Conclusion: The selection of appropriate empirical antibiotics is complex and is necessary to be guided by knowledge of the comparative ratio of multiple diseases as well as the rising prevalence of resistant strains. To increase the likelihood of survival, early diagnosis is suggested with optimal antibiotic selection based on in vitro susceptibility testing, epidemiologic patterns, and lastly, metabolic derangement treatment to be advised and required. Keywords: Bacterial Meningitis, adults, post-neurosurgery